School lunch and snacking patterns among high school students: Associations with school food environment and policies - Story Mary; Hannan Peter J; French Simone A; Neumark-Sztainer Dianne; Fulkerson Jayne A (BMC, 2005)
Abstract Objectives This study examined associations between high school students' lunch patterns and vending machine purchases and the school food environment and policies. Methods A randomly selected sample of 1088 high school students from 20 schools completed surveys about their lunch practices and vending machine purchases. School food policies were assessed by principal and food director surveys. The number of vending machines and their hours of operation were assessed by trained research staff. Results Students at schools with open campus policies during lunchtime were significantly more likely to eat lunch at a fast food restaurant than students at schools with closed campus policies (0.7 days/week vs. 0.2 days/week, p < .001). Student snack food purchases at school were significantly associated with the number of snack machines at schools (p < .001) and policies about the types of food that can be sold. In schools with policies, students reported making snack food purchases an average of 0.5 ± 1.1 days/week as compared to an average of 0.9 ± 1.3 days/week in schools without policies (p < .001). In schools in which soft drink machines were turned off during lunch time, students purchased soft drinks from vending machines 1.4 ± 1.6 days/week as compared to 1.9 ± 1.8 days/week in schools in which soft drink machines were turned on during lunch (p = .040). Conclusion School food policies that decrease access to foods high in fats and sugars are associated with less frequent purchase of these items in school among high school students. Schools should examine their food-related policies and decrease access to foods that are low in nutrients and high in fats and sugars.